Effects of mechanical and acid scarification on germination performance of Schizolobium parahyba (Fabaceae â€“ Caesalpinioideae) seeds - Salazar, Ana (Journal of Tropical Biology & Conservation (JTBC), 2019)
Improving seed germination of native species is fundamental for assisting restoration practices, particular in highly degraded ecosystems such as tropical moist forests. Tropical moist forests of Central and South America continue to decrease as a result of fragmentation and conversion of forested land to agriculture. Schizolobium parahyba is a pioneer legume tree species widely used in restoration practices due to its fast growth rate, nitrogen-fixing capacity, and wood properties. Seeds of this species exhibit low germination as a result of physical dormancy, which highly limits its propagation on a large scale. We evaluated the effects of mechanical and acid scarification treatments with solutions of sulfuric (10%, 20%) and chloridric (25%, 50%, 75%) on Schizolobium parahyba seed germination. Mechanically scarified seeds had higher germination percentage (92.5%) than seeds treated with chloridric acid (50%), sulfuric acid (33.13Â±.2.11%) or intact seeds (17.5%). Seeds soaked in 10% sulfuric acid for 1 and 5 minutes exhibited higher germination values than seeds soaked in 20% for 10 minutes. Seeds soaked in 75% and 50% chloridric acid solutions for 5 and 10 minutes had an overall higher and faster germination than seeds soaked in 25% for 1 minute. This study indicates that mechanical scarification and acid scarification with solutions of chloridric acid solutions of 50% and 75% can highly improve large-scale propagation of S.parahyba and thus assist habitat restoration and conservation practices in degraded moist tropical forests.